Kritikus tömeg : Az ügyvédség és a szakmai kamarák szerepe az elektronikus közigazgatás hazai elterjedésében (Critical mass : The role of the lawyers and the professional chambers of the judiciary in the development of e-Administration) - Bertold Baranyi (KözigazgatásTudomány)
More than twenty years have passed since Hungarian law recognised electronic documents with appropriate electronic signatures as equivalent to paper documents. In principle, this opened the way for electronic administration not only in civil law relationships but also in public authority procedures. Nevertheless, it took more than 15 years before the use of ICT tools became common practice in public administrations. Yet there was no shortage of legislation and budgetary resources. In this paper, I will examine – mainly by analysing the legal background and statistical data – how, after many years of partially or entirely fruitless attempts, electronic communication has become commonplace in legal procedures after 2018. In particular, I am looking for an answer to the question of whether lawyers and the professional chambers of the judiciary have constituted a critical mass in this, both literally and figuratively.